A study on information hiding: Steganography / Mohd Ridzuan Ahmad Hariri - Ahmad Hariri, Mohd Ridzuan (2003)
In a world where privacy is a right, many people try to find a way to hide information especially when it comes to sensitive documents and files. A person would like to send an email or file with no fear that a person aside from the recipient will read the message. Also, with all information that is on the Internet, owners of such information must protect themselves from unwanted spying, copying, theft and false representation. Recent advances in computing power and recent interest in this privacy issue has led to the development of techniques to hide messages in otherwise innocuous computer files such as digital pictures and digitized audio. This is what we called as steganography. In this dissertation, we will only provide basic knowledge of steganography with simple explanation based on research done by security experts around the world. We try to provide readers with basic idea of this concept so that they can differentiate with the concept of cryptography, which most people still confuse and assume that both terms represent the same security techniques. Throughout this thesis, we will look into the history of steganography, the basic concept and components of it and different techniques for different types of medium used to secretly communicate through this security concept. At the end of this paper, we will discuss on weaknesses of steganography in general without specifying on any medium mentioned previously.